Design of Experiments Assisted Formulation Optimization and Evaluation of Efavirenz Solid Dispersion Adsorbate for Improvement in Dissolution and Flow Properties - Mujtaba MA; Rashid MA; Alhamhoom Y; Gangane P; Jagtap MJ; Akbar MJ; Wathore SA; Kaleem M; Elhassan GO; Khalid M (Drug Design, Development and Therapy)
Md Ali Mujtaba,1,2 Md Abdur Rashid,3 Yahya Alhamhoom,3 Purushottam Gangane,4 Mohini Janardan Jagtap,4 Mohammad J Akbar,5 Sandeep Ashokrao Wathore,6 Mohammed Kaleem,7 Gamal Osman Elhassan,8 Mohammad Khalid9 1Department of Pharmaceutics, Faculty of Pharmacy, Northern Border University, Arar, Saudi Arabia; 2Center for Health Research, Northern Border University, Arar, Saudi Arabia; 3Department of Pharmaceutics, College of Pharmacy, King Khalid University, Abha, Saudi Arabia; 4Department of Pharmaceutics, Dadasaheb Balpande College of Pharmacy, Rashtrasant Tukadoji Maharaj Nagpur University, Nagpur, Maharashtra, India; 5Department of Pharmaceutics, College of Pharmacy, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 6Department of Pharmaceutics, SVP College of Pharmacy, Hatta, Maharashtra, India; 7Department of Pharmacology, Dadasaheb Balpande College of Pharmacy, Rashtrasant Tukadoji Maharaj Nagpur University, Nagpur, Maharashtra, India; 8Department of Pharmaceutics, College of Pharmacy, Qassim University, Buraidah, Saudi Arabia; 9Department of Pharmacognosy, College of Pharmacy, Prince Sattam bin Abdulaziz University, Al-Kharj, Saudi ArabiaCorrespondence: Purushottam Gangane, Email p.gangane@gmail.com Mohammed Kaleem, Email kaleemmubin88@gmail.comBackground: Efavirenz (EFZ) is an anti-HIV drug that has been administered as first-line treatment, which exhibits low solubility and poor oral bioavailability. Therefore, the current study aimed to develop a solid dispersion adsorbate (SDA) to enhance the dissolution rate and flow properties of EFZ for solid oral dosage forms.Methods: The SDA of EFZ was prepared using the fusion method with PEG-6000 and poloxamer-188 as carriers, along with avicel PH-102 and aerosil-200 as adsorbents. 32 full factorial approach was employed to formulate the SDA and evaluate the effects of two independent factors X1: the ratio of PEG-6000 to EFZ in the solid dispersion, and X2: the ratio of aerosil-200 to the solid dispersion. The dependent factors analyzed were Y1: the time required for 85% of the drug release, and Y2: angle of repose.Results: The optimized formulation (F9) was selected through numerical optimization, demonstrating the desired drug release and excellent flow properties of the pre-compressed SDA. Fourier transform infrared (FTIR) spectroscopy, Differential scanning calorimetry (DSC), X-ray diffraction (XRD), and Scanning electron microscopy (SEM) of SDA showed the transformation of crystalline to amorphous form of EFZ, which is responsible for improving drug dissolution. The direct compression method was used to prepare SDA-EFZ tablets (equivalent to 25 mg EFZ) along with plain EFZ. The dissolution efficiency increased from 50.68% for plain EFZ tablets to 96.18% for EFZ-SDA tablets. Furthermore, the cumulative percentage drug release (%CDR) from SDA tablets was nearly double that of plain EFZ tablets. Stability testing indicated no significant changes in drug content and %CDR of the SDA tablets.Conclusion: The findings of this study suggest that the SDA method is an effective approach for enhancing the dissolution and flow characteristics of EFZ and may serve as an alternative strategy for preparing solid dosage forms in commercial applications.Keywords: solid dispersion adsorbate, efavirenz, factorial design, drug delivery, in vitro dissolution